2016 ALS User Meeting Highlights. Issue 1 (2nd January 2017) - Troutman, Keri; White, Ashley; Arenholz, Elke; Fischer, Peter
Abstract : About 400 ALS users came together in early October 2016 for the annual ALS User Meeting. Attendees listened to colleagues present their research, took part in scientific workshops, interacted with exhibitors, and recognized this year's awardees.